2021
DOI: 10.3390/fi13020052
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Digital Transformation in Universities

Abstract: Industry 4.0 and Society 5.0 are reshaping the way organizations function and interact with the communities they serve. The massive penetration of computer and network applications forces organizations to digitalize their processes and provide innovative products, services, and business models. The education market is suffering changes as well, but universities seem slow to react. This paper proposes the application of an integrated digital transformation model to assess the maturity level that educational ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
79
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 22 publications
0
79
0
5
Order By: Relevance
“…The authors found that the ability and progress of the higher educational institutes have been limited and impeded by various contextual constraints. Similarly, assessing the digital maturity of the higher educational institutions, Rodríguez-Abitia and Bribiesca-Correa [40] have asserted that the higher education institutions have been lagging behind other businesses and industries when it comes to embracing digital transformation. Due to market pressure, other industries have likely been compelled to develop quicker.…”
Section: The Existing Institutional Levels Of Digital Transformationmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors found that the ability and progress of the higher educational institutes have been limited and impeded by various contextual constraints. Similarly, assessing the digital maturity of the higher educational institutions, Rodríguez-Abitia and Bribiesca-Correa [40] have asserted that the higher education institutions have been lagging behind other businesses and industries when it comes to embracing digital transformation. Due to market pressure, other industries have likely been compelled to develop quicker.…”
Section: The Existing Institutional Levels Of Digital Transformationmentioning
confidence: 99%
“…They tend to prioritize immediate results and postpone critical investments in building capabilities that are time-consuming. It is asserted that planned digitization is not being done in a particularly novel fashion, nor with the necessary financial means to execute the plan, which further exacerbates this problem [40]. This issue can be dealt with through the development of a prioritization plan for digital investments a roadmap that can guide the systematic transformation of the organization in a sequential manner.…”
Section: Digital Transformation Challenges In Higher Education Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This new revolution is being driven, principally, by advancements in areas such as artificial intelligence (AI), robotics, cloud computing, the internet of things (IoT), cyber-physical systems, big data, etc. [1,2]. Thus, industries have used these technologies to provide solutions to the growing needs of humankind; however, in order for them to continue adapting their ecosystems to the digital world, they need qualified professionals with knowledge and skills in those areas.…”
Section: Introductionmentioning
confidence: 99%
“…Industry 4.0 has been a novel topic for research for multiple independent research centers, institutes, universities, and companies in the world (Cividino et al 2019;Rodríguez-Abitia and Bribiesca-Correa 2021). Since the topic has gained momentum, there are a good number of reputed working groups discussing vision and mission of Industry 4.0 and its related technologies.…”
Section: Introductionmentioning
confidence: 99%